Habitat Suitability Mapping of Rastrelliger Brachysoma Using MODIS Image in WPP 711 - Prama Ardha Aryaguna (Faculty of Geography, Universitas Gadjah Mada, 2019)
Important factors that needs to be understood in the management of fishery resources is fish habitat. Fish habitat is an ideal water conditions of a fish species to spawn, breed, feed and grow into adults. Distribution of fish habitat can be approach using variety method, such Habitat Suitability/Species Distribution Modeling. Remote sensing analysis is effective method in providing daily oceanography information. Modis is Remote sensing imagery can be used for modeling Rastrelliger brachysoma fish habitat. Date acquired MODIS image at 28 March 2015, depend on existing field data. The results indicate that, the highest probability of Rastrelliger brachysoma fish habitat location in WPP 711 are in the middle waters of the WPP border between the deep sea of Indonesia and the Pacific Ocean. The lowest probability value for habitat of Rastrelliger brachysoma fish is in the southern shallow waters of Bangka Belitung island which is around 0.1-0.25.